Multi-Phases Fluid Activity Characteristics of Longmaxi Formation and Its Impact on Resistivity in the Changning Area, Southern Sichuan Basin, Southwest China - Cui, Yue; Li, Xizhe; Han, Lingling; Feng, Yong; Guo, Wei; Lin, Wei; Qian, Chao; Feng, Tao (Frontiers in Earth Science, 2022)
Wells with low gas content and low resistivity in the Changning area, southern Sichuan Basin were selected for this study. The burial-thermal history was reconstructed and the characteristics of multi-phase fluid activity were clarified using microscopic observation and testing of fluid inclusions in the Longmaxi shale fracture veins. Compared with wells with a high gas content and high resistivity, the influence of fluid activity on resistivity was analyzed. The results showed that the thermal evolution of the bituminous inclusions trapped in the veins has reached the stage of carbonaceous-metamorphic bitumen, and the organic matter is fully cracked for gas generation, with some organic matter exhibiting the phenomenon of “graphitization.” The synchronous fluid with bitumen was existed due to shallow burial with a middle-low maturity stage of about 280 and 292 Ma. Two phases of fluids existed in the deep burial stage, thus maturing for about 103 Ma, and the uplift stage at about 28 and 32 Ma, with high homogenization temperatures (Th) (varying from 185 to 195°C and 165–180°C). The corresponding pressure coefficients varied between 1.67 and 2.09, 1.56 and 1.92 in a moderate-strong high-pressure state. The last two phases of fluid formation in the late uplift stage for about 4 to 19 Ma and 6 to 10 Ma were characterized by low salinity at medium-low Th (varied from 140 to 155°C and 120–135°C), with pressures of 57.47–74.50 MPa and 51.44–59.41 MPa (pressure coefficients of 1.09–1.41 and 1.18–1.37), in an atmospheric-weak overpressure state. In the initial uplift stage after deep burial, the fluid closure in the Changning area was good. In contrast, the wells are filled with low gas content because of the strong tectonic forces causing the shale gas to be released and the multi-phase fluid activity that happens during the late uplift stage. New evidence indicates that the emergence of low resistance in the localized Changning area is not only related to the high degree of evolution of organic matter but is also affected by the multi-phase fluid modification in the late uplift stage.